Demodicosis in a free-ranging eurasian brown bear (Ursus arctos arctos) cub in the endangered cantabrian population, Spain - Oleaga, Álvaro; Fayos, Manena; Balseiro, Ana; Borragán, Santiago; de Pedro, Gabriel; Armenteros, José Ángel; Balsera, Ramón; Moreiro, Magalí; Sastre, Natalia; Ferrer, Lluís (Journal of Wildlife Diseases, 2024)
7 páginas, 1 figura, 1 tabla. A free-living female Cantabrian brown bear (Ursus arctos arctos) cub severely affected by mange in Asturias (northern Spain) represented the first report of demodicosis for this species. After antimicrobial, antiparasitic, anti-inflammatory, and analgesic therapy it recovered and was released back into the wild to the eastern Cantabrian brown bear subpopulation. This is a contribution to the agreement between Sociedad de Servicios del Principado de Asturias and Principado de Asturias for the maintenance of the Sanitary Surveillance Program and Wildlife Rehabilitation Center of Asturias. We thank the willingness and coordination of the administrations of Cantabria, Castilla y León, and Asturias, and the collaboration and work of all technicians and rangers involved in this case. We acknowledge especially the involvement and great work of the veterinary assistants and personnel from the three involved communitie s Wildlife Rehabilitation Centers. We also thank our colleagues from AniCura Buenavista Hospital Veterinario and especially Josep Pastor Milan from the Grup de Recerca en Ecopatologia de Fauna Salvatge (Department of Animal Medicine and Surgery, Universitat Autónoma de Barcelona) for their advice and support in brown bear s diagnosis and treatment. We thank also José Vicente López-Bao and Patricia Mateo-Toma´s from the Biodiversity Research Institute (CSIC, Oviedo University, Principality of Asturias) for providing the GPS device used to monitor the bear, under the framework of the collaboration established between these researchers and the Principality of Asturias to monitor recovered bears by using GPS units. This work was partially funded by the Principality of Asturias (PCTI 2021–2023, GRUPIN: IDI-2021-000102) and the European Regional Development Fund. Peer reviewed